Eksplorasi pemahaman siswa sekolah menengah pertama mengenai prinsip cavalieri : sejarah, konsep dan aplikasi - yulyanti -; Latifah Latifah; Hafizatunnisa Hafizatunnisa (JNPM (Jurnal Nasional Pendidikan Matematika), 2024)
Bonaventura Francesco Cavalieri was an Italian scientist famous for his Cavalieri principle. By focusing on the history, ideas, and practices of Cavalieri, this study aims to improve junior high school students' understanding of his principles. The research method used is qualitative, and data was collected through case studies, meta-analyses, and literature reviews. Various literature sources, such as textbooks, journal articles, and historical documentation related to Cavalieri's principles, were analysed to gain an understanding of how these principles can be applied in student learning. The research methods used were open-ended interviews about Cavalieri's history and an analysis of related literature. The results of the study show the level of students' understanding of Cavalieri's principles. They also inform us about the history, ideas, and some applications of these ideas.